ONTOGENY AND VARIABILITY IN THE CHEEK REGION OF HIPPARIONS FROM THE LATE MIOCENE LOCALITY HADZHIDIMOVO-1, SOUTHWEST BULGARIA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2009)
A large number of hipparion skulls from Hadzhidimovo-1 (HD) are studied herein. The sample includes individuals of various ages that allow the investigator to study their ontogenetic development. Two species of hipparion are recognized, including Hippotherium brachypus Hensel, 1862 and Cremohipparion mediterraneum Roth & Wagner, 1855. A study of the lateral aspect of the face, including the maxillary and premaxillary regions were made with specific attention paid to the placement of the preorbital and subnasal (= intermediate) fossae. The morphology of these structures are found to be of taxonomic value.  This study reveals that the most intensive growth of the cheek region in both species is the period during which the maxillary M2 erupts and that the two species have different modes of ontogenetic changes in the location of preorbital fossa. During ontogeny, the preorbital fossa of Hippotherium brachypus migrates further from the orbit, while in the C. mediterraneum samples the preorbital fossa does not migrate - it remains stationary into and throughout adulthood. This study documents intraspecific variability in preorbital fossa morphology, throughout the ontogeny for both species of hipparion under consideration.
Keywords: Late Miocene; Bulgaria; Hipparions; Preorbital fossa morphology; Ontogeny